2008
DOI: 10.1016/j.yjmcc.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of angiotensin II and PDGF-BB on migration and proliferation of coronary artery smooth muscle cells

Abstract: Angiotensin II (Ang II) and platelet-derived growth factor-BB (PDGF-BB) are associated with excessive cell migration, proliferation and many growth-related diseases. However, whether these agents utilise similar mechanisms to trigger vascular pathologies remain to be explored. The effects of Ang II and PDGF-BB on coronary artery smooth muscle cell (CASMC) migration and proliferation were investigated via Dunn chemotaxis assay and the measurement of [ 3 H]thymidine incorporation rates, respectively. Both athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In other words, TNFα release inhibition by apocynin or F-apocynin does not seem to be a result of the redox imbalance resulting from NADPH oxidase activity inhibition. Recently, Dharmarajah et al (2010) showed that the anti-platelet actions of apocynin are not the result of an inhibitory effect on NADPH oxidase or reactive oxygen species scavenging, as proposed by others (Allen and Bayraktutan, 2008), and suggested that this effect reinforces the indication of this drug as an antithrombotic agent. It confirms that the effects of apocynin extend beyond NADPH oxidase inhibition and consequent redox imbalance.…”
Section: Discussionmentioning
confidence: 81%
“…In other words, TNFα release inhibition by apocynin or F-apocynin does not seem to be a result of the redox imbalance resulting from NADPH oxidase activity inhibition. Recently, Dharmarajah et al (2010) showed that the anti-platelet actions of apocynin are not the result of an inhibitory effect on NADPH oxidase or reactive oxygen species scavenging, as proposed by others (Allen and Bayraktutan, 2008), and suggested that this effect reinforces the indication of this drug as an antithrombotic agent. It confirms that the effects of apocynin extend beyond NADPH oxidase inhibition and consequent redox imbalance.…”
Section: Discussionmentioning
confidence: 81%
“…Ang II is a main biologically active agent of the renin–angiotensin system and plays an important role in the migration of VSMCs, which contributes to restenosis after vascular injury [17,26,28]. To explore the mechanisms by which SOD2 inhibits intimal hyperplasia, we used a wound healing assay to evaluate the effect of SOD2 on Ang II-stimulated VSMC migration.…”
Section: Resultsmentioning
confidence: 99%
“…Losartan may be acting on inhibiting protein of nuclear factor κB and lead MCP-1, VCAM-1, E-selection in adhesion process to reduce, inhibiting the inflammatory response in occurrence of atherosclerosis ( 15 , 16 ). Hence, further study is required to be done.…”
Section: Discussionmentioning
confidence: 99%